2015
DOI: 10.1002/bse.1872
|View full text |Cite
|
Sign up to set email alerts
|

The Wicked Character of Sustainable Supply Chain Management: Evidence from Sustainability Reports

Abstract: Supply chains are changing their business paradigm as they strive for sustainability and not just for increasing profits. Sustainability, however, is a concept that is open to interpretation since it is based on societal and organizational values. Little is known about what companies actually mean when referring to sustainability, and how this contrasts with the understanding at different echelons of the supply chain. Diverging interpretations and translations of sustainability among stakeholders, termed wicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 84 publications
(141 reference statements)
1
66
0
3
Order By: Relevance
“…The domain of CoP is presented in the common ground of economic and ethical interests as well as responsibilities. It underscores the importance of setting a strategic direction [56], creating a shared vision [57], articulating a strategic intent of the relationship [58], and setting goals to integrate financial and environmental measurements [59]. Therefore, we searched for evidence of strategic objectives that are set and ratified by its top management and recognized through governance committees.…”
Section: Methodsmentioning
confidence: 99%
“…The domain of CoP is presented in the common ground of economic and ethical interests as well as responsibilities. It underscores the importance of setting a strategic direction [56], creating a shared vision [57], articulating a strategic intent of the relationship [58], and setting goals to integrate financial and environmental measurements [59]. Therefore, we searched for evidence of strategic objectives that are set and ratified by its top management and recognized through governance committees.…”
Section: Methodsmentioning
confidence: 99%
“…According to this perspective sustainability can be achieved at the intersection of all three dimensions (Parrish, ). Thus, organizations should endeavour to perform well on all three dimensions of the TBL (Meckenstock et al ., ). Sustainability is integrally uncertain and open to interpretation (Lazarus, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, there is little consent about sustainability in SCs among the managers (Giunipero et al ., ). Therefore, sharing information on sustainability issues will lead to a more sustainable SC within the organization (Meckenstock et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Further, the coding schemes were tested in several sustainability reports and further revised until receiving satisfactory results. Issues related to reliability were eliminated by creating coding rules while doing machine coding (Meckenstock et al, 2015). This ensured stability and reproducibility of results (Krippendroff, 2004).…”
Section: Fair Business Operationsmentioning
confidence: 99%
“…What can also be observed from Figure 3 is that the keyword occurrence for CO2 emission is highest for midstream echelon. That can be explained by the fact that midstream echelon involve production and assembly (Meckenstock et al, 2015), what is one of the main sources of CO2 emission (Martínez & Fransoo, 2017). Further, it can be observed that corruption is of high concern, where percentage of keyword occurrence decreases by moving from upstream to downstream echelon.…”
Section: Validationmentioning
confidence: 99%